Acquisition of supply market intelligence – An information processing perspective. Issue 5 (December 2020) - Lorentz, Harri; Aminoff, Anna; Kaipia, Riikka; Pihlajamaa, Matti; Ehtamo, Jesse; Tanskanen, Kari
Abstract: The capability to develop and sustain superior knowledge of markets and supply chains, or supply market intelligence (SMI), is an important element in increasing the strategic relevance of purchasing and supply management (PSM). This study draws on information processing theory (IPT) to shed light on how firms acquire SMI. In particular, the study aims to identify the drivers and mechanisms of information processing in SMI acquisition and to explore how the two constructs are related. Our findings emerged from an abductive multiple case study including 22 SMI tasks in eight case companies operating in various manufacturing industries. We find that the drivers of information processing needs in SMI acquisition are related either to uncertainty or equivocality. Uncertainty describes a situation in which decision-makers may be ignorant of a variable's value while equivocality describes a situation in which they may be ignorant of the variable's existence. We identify four structural mechanisms and three information technology mechanisms for information processing in the SMI context. We also find that equivocality seems to trump uncertainty in determining the use of the identified SMI acquisition mechanisms. In addition to elaborating IPT in the SMI context and exploring the theoretical foundations of SMI, we offer practitioners a framework for supporting the design of SMI practices in procurement organisations. Highlights: We explore how firms acquire supply market intelligence (SMI). We find the drivers of information processing needs to be uncertainty or equivocality related. We identify four structural mechanisms and three information technology mechanisms. We also find equivocality to trump uncertainty in the use of SMI acquisition mechanisms.